Мовний образ Божої Матері в Євангелії та в поезії Тараса Шевченка - Данилюк, Ніна; Danylyuk, Nina (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглянуто мовні засоби творення образу Божої Матері в Євангелії та в поезії Т. Шевченка. Виділено синонімічні одиниці на позначення ключового поняття, вказано на розширення семантики образних висловів, пов’язаних із українською дійсністю, літературними і фольклорними традиціями. The article deals with the linguistic means of the creation of image of God’s Mother in the Gospels and poetic texts by T. Shevchenko. A special attention has been paid to the peculiar features of its verbalization in the Gospels of Mathew, Mark, Luke, and John and to its reconsideration by Kobzar. A long row of synonyms that were used to represent this key notion in the works by T. Shevchenko has been defined: Матер Божа (я), Матер Божія, Матер Бога, Мати свята (я), преправедная мати, Марія, моя Марія, мати Марія, Богом ізбранна Марія, кроткая Марія, пренепорочная Марія, пренепорочная, благая; пресвятая, преправедная; пресвятая, неповинна; пречистая, пречистая в женах and others. It was also pointed out that the semantic structure of the figurative means that have associative connections with the Ukrainian reality, literary and folklore traditions has been broaden. It was qualified that the image of God’s Mother was represented in the T. Shevchenko’s works like Blessed Virgin, Mother, Woman, Ukraine. The writer has been raised the image of Holy Woman to the uppermost symbolic plane in unit with concrete and sensual features, using the book borrowed and Ukrainian language units.
Linguistic Representation of the image of God’s Mother in the Gospels and poetry by Taras Shevchenko
Keywords: мовний образ Божої Матері; поетичний текст; виразовий засіб; ключове поняття; семантика; a linguistic image of God’s mother; a poetic text; the text of the Gospels; expressive and representative means; row of synonyms; a key notion; the semantic structure